The design of linear peptides that fold as monomeric β-sheet structures - Lacroix, Emmanuel; Kortemme, Tanja; de la Paz, Manuela Lopez; Serrano, Luis (Current opinion in structural biology, 1999)
Current knowledge about the determinants of β-sheet formation has been notably improved by the structural and kinetic analysis of model peptides, by mutagenesis experiments in proteins and by the statistical analysis of the protein structure database (Protein Data Bank; PDB). In the past year, several peptides comprising natural and non-natural amino acids have been designed to fold as monomeric three-stranded β-sheets. In all these cases, the design strategy has involved both the statistical analysis of the protein structure database and empirical information obtained in model β-hairpin systems and in proteins. Only in one case was rotamer analysis performed to check for the compatibility of the sidechain packing. It is foreseeable that, in future designs, algorithms exploring the sequence and conformational space will be employed. For the design of small proteins (less than 30 amino acids), questions remain about the demonstration of two-state behavior, the formation of a well-defined network of mainchain hydrogen bonds and the quantification of the structured populations.